Marine Biodiversity Patterns and Processes, Assessment, Threats, Management and Conservation - Queiroga, H.; Queiroga, H.; Cunha, M.R.; Cunha, M.R.; Cunha, A.; Cunha, A.; Moreira, M.H.; Moreira, M.H.; Quintino, V.; Quintino, V.; Rodrigues, A.M.; Rodrigues, A.M.; et al. (Developments in Hydrobiology, 2006)
This volume presents selected contributions given to the 38th European Marine Biology Symposium, held in Aveiro, Portugal, in September 2003. Understanding the functioning of Marine Ecosystems is the first step to measure and predict the influence of Man, and to find solutions for the enormous array of problems we face today. This volume is organised according to the four subthemes of the symposium and to issues commonly perceived as relevant by scientists concerned with the study, protection and management of Marine Biodiversity: patterns and processes, assessment, threats and management and conservation. The 32 papers that make up this book represent the current research and concerns about Marine Biodiversity in Europe, and will have wide appeal to all those interested in understanding and preserving the marine ecosystems of the world's oceans. Reprinted from HYDROBIOLOGIA volume 555(2006).